The management of China's huge foreign reserve and its currency composition - Liu Pan; Zhu Junbo (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2008)
In view of the current situation of China's huge foreign reserves, this paper puts forward the concepts of foreign reserve management - regular reserve management which focuses on liquidity management, and excess reserve management focusing on security and return. The scale and the currency composition of regular reserve management can be determined by the factors of usage, while the currency composition of excess management can refer to that of the Special Drawing Right issued by the IMF.
Keywords: 330